Urban land reform in South Africa: Pointers for urban policy and planning - Huchzermeyer, Marie; Harrison, Philip; Charlton, Sarah; Klug, Neil; Rubin, Margot; Todes, Alison (University of Free State, 2019)
Urban and reform is a relatively under-researched and -considered element of the broader land-reform debate. This article reviews some of the key positions that have been explicated in the current urban land-reform debate, and seeks to extend existing contributions, fine-tune them and push the debate further. It does so by distinguishing the features of urban land, and considers these and their implications for the meaning of land reform. It also reviews the recently achieved, national policy consensus on urban development and planning, and concludes with suggestions on how to proceed with urban land reform.
Keywords: Land reform || land tenure || planning || policy || South Africa || urban